If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-7 + -1r) = -37 + 5r (-7 * 7 + -1r * 7) = -37 + 5r (-49 + -7r) = -37 + 5r Solving -49 + -7r = -37 + 5r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-5r' to each side of the equation. -49 + -7r + -5r = -37 + 5r + -5r Combine like terms: -7r + -5r = -12r -49 + -12r = -37 + 5r + -5r Combine like terms: 5r + -5r = 0 -49 + -12r = -37 + 0 -49 + -12r = -37 Add '49' to each side of the equation. -49 + 49 + -12r = -37 + 49 Combine like terms: -49 + 49 = 0 0 + -12r = -37 + 49 -12r = -37 + 49 Combine like terms: -37 + 49 = 12 -12r = 12 Divide each side by '-12'. r = -1 Simplifying r = -1
| -3n+7n=12+2n | | -8n+29=-8(n-3) | | (3+10i)+(-4+2i)= | | 5-3k=2k-6k | | 3+1-8n-6=1-5n | | -1.25r-3.5=13.5 | | 2-6d=1 | | 8x+1=48 | | 64w^2=36 | | -16+5p=p+8 | | 2x^3-9x^2+9x-20=0 | | -120=8(3r+3) | | 3(1+7x)-2x=-92 | | 7b-5b=10 | | -2(5+7v)-7=-73 | | 3c=4-c | | B-4.5=-3.2 | | -5+r+7+4r=6r-2 | | -13=5a+8a | | 8a^2(2a^2-3a+11)=0 | | (3)+2(3)-48= | | -6n+4n=16 | | 98=7(k-5) | | -10+10x=160 | | 11.04+6(4.9-3.7)= | | B-4.5=3.2 | | Y=x*3-3x*2+12 | | 210=-10(-2+x) | | 6h=-48 | | lnx=0.8 | | 20-8+4= | | y=(2x-1) |